FORMATION OF INTUITIVE ABILITY IN PEDAGOGICAL ACTIVITY: MOTIVATION, FORECASTING AND CREATIVE THINKING (Universal International Scientific Journal, 2026)
This article analyzes the psychological, pedagogical and cognitive foundations of the development of intuition in the process of pedagogical activity. Intuition is interpreted as an important mechanism in the cognitive activity of a person, and its inextricable connection with motivation, forecasting, imagination, memory and creative thinking is highlighted. The study reveals the functions of intuition in pedagogical activity - regulatory, compensatory, orientational, integrative and prognostic aspects. It also substantiates the differences between intuitive and impulsive decisions. The article analyzes on a scientific basis the possibilities of developing students' intuitive abilities through the use of creative texts in native language education. Creative texts are evaluated as an effective tool for activating holistic perception, aesthetic choice and cognitive synthesis in students.
Keywords: intuition; creative text; pedagogical activity